Synthesis of phenanthroline substituted five-nuclear phthalocyanine zinc complex and exploring of photochemical and sono-photochemical properties - Unlu, Seda; Elmali, Fikriye Tuncel; Atmaca, Goknur Yasa; Erdogmus, Ali (PERGAMON-ELSEVIER SCIENCE LTD, 2024)
Sono-photodynamic therapy (SPDT) which is the combination of photodynamic therapy (PDT) and sonodynamic therapy (SDT) is an alternative and efficient method among cancer treatments achieving high singlet oxygen quantum yield. This study aimed to synthesize Schiff base substituted Zn phthalocyanine containing phenanthroline group to obtain suitable sono-photosensitizer. The target phthalocyanine (4) was obtained by cyclotetramerization reaction of phenanthroline-Zn(II) complex substituted phthalonitrile (3) with zinc acetate. The synthesized compounds were characterized by various spectroscopic techniques including FT-IR, Mass, UV-Vis, and 1H NMR spectroscopy. The singlet oxygen quantum yield was calculated in both photochemical and sonophotochemical method for compound 4. While the phi Delta value was calculated as 0.72 for photochemical method, the phi Delta value reached to 0.98 for sono-photochemical method.
Keywords: Sono-photochemistry; Photochemistry; Zinc phthalocyanine; Schiff base; Phenanthroline; PHOTODYNAMIC THERAPY; SONODYNAMIC THERAPY; CANCER; EFFICACY; Chemistry; Crystallography